Passing sequence towards field goals and penalty corners in men’s field hockey / Muhammad Ariff Engliman - Engliman, Muhammad Ariff (2014)
Modem field hockey relies on effective game play within well-structured ball movement as its multidimensional factors in contributing field goals and penalty comers. Therefore, the objective of the study was to analyse the effect of passing sequences (longer passing sequence and shorter passing sequence) towards field goals and penalty comers in men’s field hockey. Passing sequence referred to how many touches or passing made towards obtaining field goals or penalty comers won by the attacking team. Longer passing sequence was passing made more than five times, meanwhile shorter passing sequence was passing made less than four times. Analysis of 24 footages/ video taken from World Hockey League Semi Finals at Johor Bahru, 2013, including 8 countries (Germany, Argentina, England, Korea, Malaysia, Japan, Pakistan, and South Africa) competing to qualify for World Cup 2014. The analytical process focused on two different passing sequences in attacking on field goals and penalty comers in men’s field hockey. Two reliability tests, (intra and inter observer test) were conducted on researcher before going through the data collection process. All the footage/video were analysed by using computerized analysis software (SPORTCODE ELITE). A Wilcoxon Signed Ranked Test was deemed the appropriate statistical method to determine the effect of this study. Results showed that there were significant different between shorter passing and longer passing sequence towards field goals when, (z = -4.05, p < .05), and the median for shorter passing sequences is greater than that of the longer passing sequences towards field goals. Meanwhile, for penalty corners, showed that shorter passing sequences were more effective and beneficial in men’s field hockey when the data indicate (z = -4.29, p < .05), and the median for shorter passing sequences is greater than that of the longer passing sequences towards penalty comers. Moreover other findings from this study also support that shorter passing sequence is more effective during attacking in men’s field hockey when shown that D penetration more often occurred compare to longer passing sequence (z = -4.28, p < .05). It is important for all team to use an effective tactical play during attacking task especially for sports which emphasize on striking invasion like field hockey. Furthermore, in modem field hockey, less sequence of passing suit with shorter the times to obtain field goals or penalty comers before the opponent reorganize their defensive line. These findings could be used by any level of field hockey coaches to implement during training as to improve and enhance their team attacking ability during competition. Further research could to be conducted on the correlation between passing sequence and basics skills performance in field hockey.